The Neuromodulator Effect of Vagal Nerve Stimulation as the Treatment of Medically Refractory Epilepsy in Comparison with Surgical Approach: A Systematic Review - Anas, Muhammad Al; Ritonga, Dwi Herawati (Talenta Universitas Sumatera Utara, 2022)
Background: Restorative options in medically refractory epilepsy are restricted to ablative brain surgery, the trial of antiepileptic medications, or palliative procedures. Vagal nerve stimulation (VNS) is an accessible palliative method of which the mechanism of action isn't well understood, yet with set up adequacy for medically refractory epilepsy and low occurrence of incidental effects. Objectives: This systematic review aimed to evaluate the action of epilepsy treatment options. Methods: We searched for relevant studies published in 2016-2021 with PRISMA charts. For English published statistical analyses, we include all studies conducted on pediatric epileptic patients who have undergone epilepsy surgery and VNS. Results: Antiepileptic impacts of VNS incorporate expanded movement of the locus coeruleus (LC) neurons with a raised norepinephrine (NE) discharge in the hippocampus, cortex, and amygdala. VNS-modulatory consequences for other synapse frameworks such as cholinergic, GABAergic, and glutamatergic depend on the activation of the LC-NE pathway. While in pediatric epilepsy, early surgical intervention is frequently recommended to work on cognitive and behavioral outcomes that unequivocally portray the epileptogenic zone. Conclusion: The general rate of complication caused by epilepsy surgery was sensibly low (5%), suggesting that epilepsy medical procedures, particularly primarily temporal lobe resection, can be safe preferably with recent procedure options, while VNS could be more effective as therapy begins at early stages pre- or post-seizure onset to decide the preventative role of VNS in human epileptogenesis when the treatment is given promptly.